Fostering Community Participation: The Role of Forestry Extension Officers in Maximizing Social Capital for National Park Conservation - Suswadi; Irawan, Norbertus Citra; Esthi, Raniasari Bimanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The lack of community involvement poses a significant obstacle that may impede the achievement of success in the conservation partnership program between the Mount Merbabu National Park (MMNP) authority and the local community. This study serves a purpose and presents a new approach by investigating the impact of human and social capital on community engagement in the conservation partnership program, with the mediation of the extension worker’s role. This location was determined using a purposive method, focusing primarily on three villages surrounding MMNP, Indonesia. The sampling technique employed was simple random sampling, where 30 respondents were chosen from each village, resulting in a total sample size of 90 respondents. This study examines the variables using the Structural Equation Model (SEM) - Partial Least Squares (PLS) approach. Social capital has a positive and significant impact on community engagement through forestry extension workers, while human capital does not affect community conservation partnership involvement through the same workers. This study recommends enhancing social capital to increase community participation in conservation initiatives. Forestry extension officers should improve communication, social networks, and environmental competency to encourage greater community involvement in environmental protection. Keywords: community engagement, extension workers role, forest conservation, human capital, social capital